Solvable Many-Body Models of Goldfish Type with One-, Two- and Three-Body Forces - Bihun, O.; Calogero, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
The class of solvable many-body problems ''of goldfish type'' is extended by including (the additional presence of) three-body forces. The solvable N-body problems thereby identified are characterized by Newtonian equations of motion featuring 19 arbitrary ''coupling constants''. Restrictions on these constants are identified which cause these systems – or appropriate variants of them – to be isochronous or asymptotically isochronous, i.e. all their solutions to be periodic with a fixed period (independent of the initial data) or to have this property up to contributions vanishing exponentially as t→ ∞.